Lexicon for blood‐based early detection and screening: BLOODPAC consensus document - Christina A. Clarke; Breeana L. Mitchell; Girish Putcha; Emma Alme; Peter Bach; Jonathan P. Beer; Tomasz M. Beer; Michelle A. Beidelschies; Jody Hoyos; Eric Klein; Peter Kuhn; Nancy Krunic; et al. (Clinical and Translational Science)
Abstract In the United States, 2.0 million new cancer cases and around 600,000 cancer deaths are estimated to occur in 2024. Early detection gives cancer patients the best chance for treatment success. Currently, cancer screening in the general population is recommended for a limited set of cancers; as a result, most cancer types are not regularly screened. Thus, in recent years, we have seen a wave of novel, non‐invasive, single‐ and multi‐cancer detection tests (SCD and MCD), promising detection of cancer signals prior to the onset of symptoms and/or clinical diagnosis. To accelerate the development, access, and adoption of these tests, the Blood Profiling Atlas in Cancer (BLOODPAC) Consortium, a collaborative infrastructure for developing standards and best practices, established the Early Detection & Screening (ED&S) Working Group. The early detection space is in need of consensus around definitions for SCD and MCD tests that harmonize terminology across diverse stakeholders, thereby reducing communication barriers and ultimately advancing the discipline. To this end, the ED&S Working Group compiled a lexicon of terms, chosen based on perceived importance, frequency of use, lack of clarity, and unique challenges in the context of SCD and MCD tests. This lexicon was submitted to the FDA for their feedback, which was incorporated. In this work, we present the first installment of the lexicon, consisting of 14 primary terms, that will be part of an online dictionary and provide a foundation for future projects of BLOODPAC's ED&S Working Group.